1994
DOI: 10.2116/analsci.10.943
|View full text |Cite
|
Sign up to set email alerts
|

Stability of an Agar-Supported Bilayer Lipid Membrane and Its Application to a Chemical Sensor

Abstract: Lipid membranes made of lecithin and cholesterol were formed by self-assembly in a small aperture on an agar support. The membranes exhibited an average electric resistance of 135 Gfl and a capacitance of 0.43 µF/cm2. Gramicidin, known to form a channel in uni-lamellar lipid bilayers, reduced the electric resistance to a Mf level, thus showing the membranes to be of a uni-lamellar bilayer type. The membrane stability was investigated against perturbation with electric potentials and against mechanical agitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…BLM-like membranes were formed either on top of an agarose cushion exposed to electrolyte [24][25][26][27][28][29] or sandwiched between two agarose sheets. 20,30,31 Additionally, monolayer lipid membranes were transferred to agarose films by means of LangmuirBlodgett transfer.…”
Section: Introductionmentioning
confidence: 99%
“…BLM-like membranes were formed either on top of an agarose cushion exposed to electrolyte [24][25][26][27][28][29] or sandwiched between two agarose sheets. 20,30,31 Additionally, monolayer lipid membranes were transferred to agarose films by means of LangmuirBlodgett transfer.…”
Section: Introductionmentioning
confidence: 99%
“…6 The procedure for forming a planar BLM on agar or agarose gel has been published. 9,10 Briefly, a small diameter (~0.5 mm) Teflon tubing is filled with a hot hydrogel solution (e.g., 0.3 g agar in 15 ml of 3 M KCl). For electrical connection as well as serving as a reference electrode, an Ag/AgCl wire is inserted at one end.…”
Section: Blms On Agar and Agarose Gels (Sb-blms)mentioning
confidence: 99%
“…The results obtained with these s-BLMs compare favorably with conventional BLMs containing related compounds such as valinomycin. 5,10 Umezawa and his colleagues, for example, earlier reported in an elegant comparative study on the potentiometric responses between a valinomycin-based BLM and a solvent polymeric membrane. Minami et al 10 found that the detection limit, dynamic range and optimum valinomycin concentration for the K + ion-induced Nernstian slope for the BLM were comparable to those of the polymeric membranes.…”
Section: Ion Sensorsmentioning
confidence: 99%
See 2 more Smart Citations